KEBERARTIAN KAMPUNG SAMPIREUN RESORT & SPA BAGI KONDISI SOSIAL EKONOMI MASYARAKAT SEKITAR KAWASAN - Riska Rahmayani, - (2009)
Kampung Sampireun Resort & Spa is one of the resorts has been becoming the pride of Kabupaten Garut. This research is conducted as the writer would like to identify the influence of Kampung Sampireun's existence to the social and economic condition of people around it, that are people from Desa Sukakarya, Kecamatan Samarang, Kabupaten Garut. The term social and economic condition could be defined as the living condition and the prosperity level of the people in order to fill their daily life needs. It would be investigated from these three aspects: their livelihoods, income, and education. The method employed in this research is a survey method which observes the object of the research directly. The sample of this research is people around the Kampung Sampireun Resort & Spa, which are 87 family leaders from Desa Sukakarya RW 01, 02, 08, and RW 10. The writer conducted the direct observation, interviewing, giving out some questionnaires, and literatur study for collecting the data. In processing and analizing the data, the writer employed the qualitative and quantitative method. The data from respondents processed by using the percentage formula, Chi Square analysis and coefficient of contingency. The result of this research shows that Kampung Sampireun Resort & Spa has shifted livelihoods and increased sorrounding society income, but it has not given any contributions to the education sector would be done this year. The most influencial aspect of the existance of Kampung Sampireun Resort & Spa to the social economic condition of the surrounding society is that there are more labor forces available in tourism and in many other fields. Generally, the perception of the people of Desa Sukakarya shows the symptoms of Apathy, the villagers think that tourists have been their customary, and their interaction with them is dominated with the commercial purpose. To make it more functional, the existance of the resort should be initiated with and agreement with people arround it and a concern to the environmental. Culture and religion also become some other aspects which should be concerned with. As the resort grows larger, it is also aimed that the return from the expanding of the resort has to be given back to people around the resort.